Change in agreement between stroke survivors and their significant others on the severity of restrictions of functioning in a 1-year follow-up. Issue 4 (December 2015) - Tarvonen-Schröder, Sinikka; Laimi, Katri; Kauko, Tommi; Saltychev, Mikhail
Abstract : The aim of this study was to assess the agreement between stroke survivors and their significant others on the severity of restrictions of functioning and to investigate the change in this agreement in a 1-year follow-up. The 41 stroke survivors and their significant others assessed the severity of impairment at the end of in-patient interdisciplinary neurorehabilitation and 1 year later using a structured form based on International Classification of Functioning, Disability and Health (ICF). The main outcomes were as follows: (i) change in the severity score of each observer on a particular restriction (intraobserver change); (ii) change in difference in severity scores within each observer pair (interobserver change); and (iii) change in agreement between interobserver differences in severity scores during a 1-year follow-up. The significant others identified more restrictions at baseline (256 vs. 194 ICF categories, χ 2 P= 0.004) than the rehabilitants did. After 1 year, this difference became insignificant (218 vs. 207 ICF categories, χ 2 P =0.59). The severity of perceived restrictions did not differ over time (all P >0.05). Although significant others rated the restrictions as slightly more severe than rehabilitants, the difference was not significant. The agreement between severity scores within observer pairs showed a tendency to improve during a 1-year follow-up. Statistically significant improvements in Cohen's κ agreement were found for muscle power (0.6–1.0), walking (0.7–0.9), eating (0.7–1.0) and immediate family support (0.5–0.8). The agreement between stroke survivors and their significant others on the severity of the restrictions of functioning showed a tendency to improve over time.